Syngas from Reforming Methane and Carbon Dioxide on Ni@M(SiO2 and CeO2) - Derun Hua; Jian Li; Xiaowen Guo; Xinning Lu; Hao Ding; Rengui He (Nanomaterials)
The accumulation of greenhouse gasses (CH4 and CO2) results in an increase in the temperature of the atmosphere. The conversion of greenhouse gasses into chemicals and fuels with high added value benefits not only the environment but also energy development. A promising and well-studied process is the reforming of methane, where CH4 and CO2 are converted into syngas (CO and H2). However, catalysts hinder the development of the process. In this paper, we investigate the conversion of CH4 and CO2 into syngas using a thermal conversion method. The catalysis performance was evaluated by reforming methane. Ni-based catalysts were prepared by different methods. All prepared catalysts were characterized (XRD, HRTEM et al.), and the process of reforming carbon dioxide–methane was carried out in a fixed bed reactor under atmospheric pressure and a high temperature. Ni(M) @CeO2 is one of the most popular options due to the role of CeO2. The deposition of coke in Ni-based catalysts was investigated.